2017
DOI: 10.1371/journal.pone.0177044
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity and progression of late onset Alzheimer’s disease: A systematic review

Abstract: BackgroundAlzheimer’s disease is a neurodegenerative syndrome characterized by multiple dimensions including cognitive decline, decreased daily functioning and psychiatric symptoms. This systematic review aims to investigate the relation between somatic comorbidity burden and progression in late-onset Alzheimer’s disease (LOAD).MethodsWe searched four databases for observational studies that examined cross-sectional or longitudinal associations of cognitive or functional or neuropsychiatric outcomes with comor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 52 publications
5
75
2
3
Order By: Relevance
“…9 Other studies have shown AD progression is likely to be influenced by noncognitive factors, such as depressive symptoms and comorbid disease burden as well. 6,7 These findings suggest that combining disease-related characteristics with other information on the patient's profile may improve the prediction of AD progression. Such a prediction may not only provide valuable prognostic information for patients and caregivers but also help us to target patients who are most likely to benefit from interventions aimed at slowing disease progression.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…9 Other studies have shown AD progression is likely to be influenced by noncognitive factors, such as depressive symptoms and comorbid disease burden as well. 6,7 These findings suggest that combining disease-related characteristics with other information on the patient's profile may improve the prediction of AD progression. Such a prediction may not only provide valuable prognostic information for patients and caregivers but also help us to target patients who are most likely to benefit from interventions aimed at slowing disease progression.…”
Section: Introductionmentioning
confidence: 93%
“…cognition), even though the importance of a multidomain approach in dementia has been repeatedly reinforced. 3, 5, 6 The few studies that have analyzed multiple outcomes of AD simultaneously, have shown correlation between rates of change in cognition and daily functioning. 2, 7, 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional status indicators were assessed using anthropometric measurements, including weight, height, arm span, waist circumference, hip circumference, mid-upper arm circumference (MUAC), and calf circumference. The measurement of these figures was done according to standard protocols [14]. The Body Mass Index (BMI, kg/m 2 ) was calculated as the body weight in kilograms divided by the squared standing height in meters.…”
Section: Nutritional Status Body Composition and Blood Pressurementioning
confidence: 99%
“…The upstream causative mechanisms of physical frailty include systemic inflammation, cell senescence, hormonal changes, and mitochondrial dysfunction [11,12]. These mechanisms are reported to exacerbate neurodegenerative and vascular damages associated with cognitive decline and dementia [13,14].…”
Section: Introductionmentioning
confidence: 99%